Study of computed tomography perfusion in traumatic cerebral contusion - Ahmad Helmy, Abdul Karim (2009)
Study of computed tomography perfusion (CTP) in traumatic cerebral contusion Head injury is listed as the sm principle cause of death in Ministry of Health (MOH) hospitals with percentage of 6.07% (Health Statistics MOH, 2004). The prevalence rate of cerebral contusion was recorded as 15.0%(Wintermark et al., 2004). Non-enhanced CT (NECT) brain is a sensitive primary diagnostic tool in the evaluation of patients with head injury. On NECT brain, pericontusional hypodensity area represents oedema. However, its perfusion disturbance could not be determined from plain CT scan. CTP provides information regarding ischaemic injuries related to the trauma and able to determine any evidence of pericontusional ischaemia. Reduction of perfusion can lead to unfavourable outcome. This study aims to determine perfusion status of pericontusional hypodensity area and correlation with clinical outcome. Ten patients involved in motor vehicle accidents (MV A) fulfilled the inclusion and exclusion criterias and hence enrolled in this study from July 2007 to November 2008 .. NECT scan of the brain was done on admission to confirm presence of contusion and followed by CTP. The data were analyzed at the CT workstation. Pericontusion areas were divided into four sections in relation to distance from the skull. Distance and size of contusion were measured from NECT scan. The region of interest were drawn based on hypodensity and CTP colour map. Each parameters of perfusion were produced by the perfusion software and were analyzed. CTP results were categorized as normal, ischaemia or infarct Clinical outcome was evaluated using GOS after 6 weeks post trauma.